The Mo catalyzed graphitization of amorphous carbon: an in situ TEM study. Issue 59 (24th October 2019) - Sharma, Subash; Paudel Jaisi, Balaram; Araby, Mona Ibrahim; Elnobi, Sahar; Ayhan, Muhammed Emre; Kalita, Golap; Tanemura, Masaki
Abstract : In situ TEM experiments were carried out to demonstrate the catalytic properties of Mo during graphene synthesis. Abstract : For the fabrication of graphene-based nano-scale interconnects, precise control over their position and proper nanoscale soldering are essential. In this work, we report the Joule heat-induced conversion of amorphous carbon to graphene in an in situ TEM setup, using Mo as a catalyst. The catalytic role of Mo during graphene formation has been less explored compared to other metals like Cu or Ni. Compared to metals like Cu, Mo is less subject to electromigration and brittleness, making it suitable for high-temperature electronics. We found that during the electromigration of Mo, amorphous carbon nanofibers (CNFs) can be converted to highly crystalline few-layered graphene. It was also found that during the graphene formation process, agglomerated Mo particles can be effectively channeled to the end of graphene by voltage-driven electromigration. An agglomerated Mo particle between the probe and graphene acted as a soldering agent, providing the prospect of the further exploration of Mo as a nanoscale soldering material. This work explores the double role of Mo: as a catalyst for graphene synthesis and as a soldering material.